Genome-wide association study for milled grain appearance traits using multi-parent advanced generation intercross population in rice - Xiaoxiang, Li; Jindong, Liu; Liang, Guo; Xiucai, Wei; Yamei, Wang; Xiaowu, Pan; Zheng, Dong; Wenqiang, Liu; Licheng, Liu; Jun, Min; Sanxiong, Liu; Ye, Guoyou; et al. (Elsevier, 2023)
The identification of loci and markers associated with milled grain appearance traits is essential for breeding high-yielding and good-quality rice variety. To detect stable loci for these characteristics, grain length (GL), grain width (GW), grain length/width (GLW), chalkiness degree (CD), chalky-grain rate (CR) and translucency degree (TD) of 378 rice lines were evaluated in three seasons. These lines were derived from a multi-parent advanced generation intercross (MAGIC) population, and genotyped using genotyping-by-sequencing, which identified 52 503 single nucleotide polymorphism (SNP) markers for genome-wide association study (GWAS). A total of 24 loci for milled grain appearance traits were detected, explaining 3.6%–27.7% of the phenotypic variations, among which, 10 were identified in the similar locations to known genes or QTLs, while 14 were believed to be novel. In addition, 15 loci exhibited effects across two or more traits, and 18 loci were stable across two or more seasons. Further, we identified four candidate genes possibly involved in signal transduction pathways of plant hormones and starch synthesis for milled rice using qRT-PCR validation. This study provides novel insights into the genetic basis underlying milled rice, and the significantly associated SNP markers and accessions with a larger number of favorable alleles could prove useful in improving grain yield and quality through breeding efforts.